Research on Grid-side Traction Converter with Low-order Harmonic Current Suppression Capability - LIU Tong; LIU Wensheng (机车电传动)
In order to suppress the low-order harmonic current caused by the grid harmonic voltage and the DC pulsating voltage in the single-phase PWM rectifier, a control algorithm combining the DC-link voltage notch filter and the proportional resonance control was proposed. The N-order notch filters was placed on the back of the voltage loop, and the notch filter design and discretization method was discussed to achieve the elimination of DC-side pulse voltage interference. Proportional resonant controllers with anti-grid frequency fluctuation and phase angle compensation was adopted in current inner loop. The parameters of the fundamental frequency proportional resonant controller were designed by the root locus method, and the harmonic resonant controller was designed by using the amplitude-frequency characteristic to analyze the control ability of current loop to the AC signal. The correctness and feasibility of the algorithm were validated by simulation.